1992
DOI: 10.2307/2937114
|View full text |Cite
|
Sign up to set email alerts
|

Life History Diversity of Canopy and Emergent Trees in a Neotropical Rain Forest

Abstract: To assess the diversity of tropical tree life histories, a conceptual framework is needed to guide quantitative comparative study of many species. We propose one such framework, which focuses on long-term performance through ontogeny and over the natural range of microsites. For 6 yr we annually evaluated survival, growth, and microsite conditions of six non-pioneer tree species in primary tropical wet forest at the La Selva Biological Station, Costa Rica. The species were: Lecythis amp/a, Hymenolobium mesoame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
639
2
32

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(703 citation statements)
references
References 56 publications
30
639
2
32
Order By: Relevance
“…Harper (1977) described such plant populations as being largely composed of "suppressed weaklings", implying that only a few individuals exhibited much greater than average growth while most individuals tended to cluster around low growth values, especially under density stress. Similar effects were found in a Costa Rican rain forest (Clark and Clark 1992), and in Sarawak, Malaysia (Primack et al 1985). Interestingly, in 1992-1996 skewness and kurtosis values were reduced, suggesting less competitive interactions under unfavourable growth conditions (although this effect was not obvious with conservative cutoffs).…”
Section: Growth Variations In Relation To External Environmental Factorssupporting
confidence: 64%
See 1 more Smart Citation
“…Harper (1977) described such plant populations as being largely composed of "suppressed weaklings", implying that only a few individuals exhibited much greater than average growth while most individuals tended to cluster around low growth values, especially under density stress. Similar effects were found in a Costa Rican rain forest (Clark and Clark 1992), and in Sarawak, Malaysia (Primack et al 1985). Interestingly, in 1992-1996 skewness and kurtosis values were reduced, suggesting less competitive interactions under unfavourable growth conditions (although this effect was not obvious with conservative cutoffs).…”
Section: Growth Variations In Relation To External Environmental Factorssupporting
confidence: 64%
“…However, longer term studies (without dendrometers) have suggested that on an annual basis the relationship between rainfall and growth might become negative as the average annual rainfall increases. Thus, a four year study in a dry evergreen rainforest of Ghana (Swaine et al 1990;annual rainfall: 570-910 mm, at least eight months with less than 100 mm) found that faster growth occurred during higher rainfall years as expected based on seasonal patterns, whereas studies lasting up to eight years in moist forest sites of Panama (Condit et al 1993a(Condit et al , 2004annual rainfall: 2030-2892.5 to 4.5 months with less rainfall than potential evapotranspiration) found higher growth rates in saplings and several large trees during a drought year, and similarly a six-year study in a wet forest of Costa Rica (Clark and Clark 1992; annual rainfall: 3859 mm, no months with less than 100 mm) found highest median annual growth rates in the smallest and largest size classes during the lowest rainfall years and lowest growth during the highest rainfall years in most of the species studied. Similarly, a short twoyear dendrometer study in a wet evergreen forest of India (Pelissier and Pascal 2000; annual rainfall >4000 mm, five months with less than 100 mm) also showed higher average annual growth during the relatively drier year.…”
Section: Introductionmentioning
confidence: 66%
“…Kitajima (1994) points out that these traits are better correlated with survivorship in shade and not just with the reputed successional class of species. It is possible that the lack of a consistent trend of variation of these parameters may have emerged here because of the attempt to correlate them with the successional position of the species at adult stage, as species requirements and even growth responses may change with ontogeny (Clark & Clark 1992). Despite these considerations, the RGR still seems to vary consistently with the successional ranking, as discussed above.…”
Section: Discussionmentioning
confidence: 89%
“…Uhl et al (1988) and Clark & Clark (1992) found higher mortality among individuals of less than 10 cm diameter. According to Felfili (1995b), the greater mortality among individuals belonging to the smallest diameter classes should result from the lower competition capacity in relation to the larger trees, which occupy the upper strata.…”
Section: Discussionmentioning
confidence: 92%